A proposed treatment for pathogenic enveloped viruses having high rates of mutation or replication. (22nd July 2020) - Roe, Kevin
Abstract: Several enveloped viruses, particularly some RNA viruses, have high rates of mutation or replication, which can make them virulent pathogens in humans and other mammals. A proposed treatment could use synthesized proteins to mask pathogenic viral surface proteins to quickly induce an immune attack on specific enveloped viruses by using existing immune cells. One treatment could inject dual‐protein ligand masks into patients' bloodstreams to mask pathogenic surface proteins used to infect mammalian cells. The mammalian immune system already uses an analogous, more complex structure called a pentraxin to neutralize some pathogens by connecting their surface proteins to immune cells. And several types of antiviral peptides have already experimentally demonstrated effectiveness in blocking various viral pathogen infections. These treatments offer advantages, especially for currently untreatable viral pathogens. Furthermore, using dual‐protein ligands and the antigenic memory of some sub‐populations of NK cells would also allow the creation of defacto vaccines based on a host's NK cells, instead of vaccines utilizing CD4 and CD8 α:β T cells, which are limited by the requirement of MHC presentation of the target antigens to α:β T cells. Targeted NK cell vaccines could attack host cells latently or actively infected by intracellular pathogens, even host cells having pathogen downregulated MHC antigen presentation. Eight postulates concerning the effects of pathogen mutation, or change in phenotype from genetic recombination or rearrangement, and replication rates on pathogen vs host dominance are also listed, which should be applicable to viral and non‐viral pathogens.